Tinjauan Kritis Tentang Efektivitas Ekspository Learning dalam Pembelajaran - Aisyah Haura Firdaus; Yola Medistya; Tauliah Puji Lestari; Suyuti Suyuti (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Expository learning is a teaching strategy that emphasizes direct, systematic, and structured delivery of content from teacher to students. Although it is considered efficient in conveying factual and procedural knowledge, its effectiveness in supporting 21st-century learning demanding active participation and critical thinking is still debated. This study aims to critically examine the effectiveness of expository learning through a literature review of national journals published between 2017 and 2025. The method used is library research with a descriptive-qualitative approach and content analysis technique. The findings reveal that expository learning is effective across educational levels for conceptual material, but its weakness lies in limited student engagement. Supporting factors such as teacher competence, instructional media, and student readiness significantly influence its success. This study also finds that expository learning remains relevant when combined with interactive methods such as discussions and projects. Practically, teachers are encouraged to design more adaptive expository learning to maintain its effectiveness in today’s educational context.